2019
DOI: 10.5539/jas.v11n11p156
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterization of Cephaleuros virescens Occurring in Mango Trees

Abstract: The objective of this work was to accomplish the micromorphological characterization of the causal agent of the algal spot in ‘Amrapali’ mango trees. Therefore, ‘Amrapali’ mango leaves exhibiting symptoms of algal spots were used for making microscope slides, on which the pathogen somatic and reproductive structures were measured. The dimensions obtained for sporangiophores and sporangia were 245.5-545.6 × 10.5-19.1 μm and 21.4-34.2 × 16.3-24.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Penyakit karat daun kelapa sawit yang disebabkan oleh alga Cephaleuros virescens sudah lama dilaporkan keberadaannya di perkebunan kelapa sawit di Indonesia (Susanto dan Sudhart 2002). Alga C. virescens memiliki lebih dari 600 jenis tanaman inang, termasuk komoditas perkebunan bernilai ekonomi tinggi (Han et al 2011;Malagi et al 2011;Pitaloka et al 2015;Ponmurugan et al 2010;Ponmurugan et al 2009;Sunpapao et al 2017;Sunpapao et al 2016;van Eesvelde et al 1993;Vasconcelos et al 2018;Vasconcelos et al 2016). Perkembangan alga C. virescens terutama dipengaruhi oleh kelembapan udara relatif.…”
Section: Pendahuluanunclassified
“…Penyakit karat daun kelapa sawit yang disebabkan oleh alga Cephaleuros virescens sudah lama dilaporkan keberadaannya di perkebunan kelapa sawit di Indonesia (Susanto dan Sudhart 2002). Alga C. virescens memiliki lebih dari 600 jenis tanaman inang, termasuk komoditas perkebunan bernilai ekonomi tinggi (Han et al 2011;Malagi et al 2011;Pitaloka et al 2015;Ponmurugan et al 2010;Ponmurugan et al 2009;Sunpapao et al 2017;Sunpapao et al 2016;van Eesvelde et al 1993;Vasconcelos et al 2018;Vasconcelos et al 2016). Perkembangan alga C. virescens terutama dipengaruhi oleh kelembapan udara relatif.…”
Section: Pendahuluanunclassified
“…Among such organisms, the algae of the Cephaleuros genus has higher reputation with the scientific community, particularly because it is widely distributed throughout tropical and subtropical regions worldwide (Gokhale & Shaikh, 2012). According to Malagi et al (2011), in Brazil, incidence of algae spots has already been reported in avocado, black pepper, acerola (Malpighia emarginata), annatto, cashew, black tea, yerba mate, mango (Vasconcelos et al, 2019), coffee, soursop, apple, cassava, basil, guava, olive and citrus cultivars. However, molecular studies with this genus are incipient, making the morphological and symptomatic characterization crucial for the species identification.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Cephaleuros morphological characterization, there is no standardization as to which characters should be measured and, although measures of the most known characters have already been published, some need to be reevaluated (Rindi & López-Bautista, 2008). Additionally, some isolates of Cephaleuros have been identified through the sequencing of conserved genes, occurring in mango trees (Vasconcelos et al, 2018). As a result, this study was designed to carry out the morphological characterization and molecular identification of the causal agent of algae spots in Brazilian mahogany.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2011). Characterization and identification of parasitic algae involve observation, counting, measurements and description of algal length, the width of sporangium and sporangiophore under the microscope in addition to determining the number as well as the diameter of lesions per leaf (Ponmurugan et al, 2009;Vasconcelos et al, 2018). Morphological characterization of the algae structure was done by using leaf samples.…”
Section: Collection Of Leaves With Symptoms Of Red Rustmentioning
confidence: 99%
“…Rain is essential for the production and dispersal of zoospores (Chanthapatchot and Satjarak, 2019;Ponmurugan et al, 2009). In studies on the Cephaleuros, morphological, sporangiophore and sporangia are commonly estimated to characterize Cephaleuros species (Han et al, 2011;Vasconcelos et al, 2018). Therefore, the objective of this study was to carry out an assessment of red rust disease of mango and identify the pathogen or agent in Cameroon.…”
Section: Introductionmentioning
confidence: 99%